Antara Ego dan Bukti Sosial: Perspektif Keuangan Keperilakuan pada Keputusan Investasi di Galeri Investasi UNUSIDA: Between Ego and Social Proof: A Behavioral Finance Perspective on Investment Decisions at the UNUSIDA Investment Gallery - achmad zaki (TALI JAGAD JOURNAL, 2026)
This study aims to empirically examine the influence of psychological biases specifically overconfidence, confirmation bias, and herd behavior on investment decision-making among young investors. The research focuses on students affiliated with the Capital Market Study Group (KSPM) at the Investment Gallery of Universitas Nahdlatul Ulama Sidoarjo (UNUSIDA). A causal quantitative approach was employed, with the population consisting of all KSPM members. Using a census (total sampling) technique, a sample of 32 students actively trading in the capital market was selected. Data were collected through structured questionnaires using Likert scales, which underwent rigorous validity and reliability testing. The data were subsequently analyzed using multiple linear regression analysis via statistical software. The results indicate that all three variables were found to have a positive and significant impact on investment decisions. A key finding reveals that herd behavior is the most dominant factor in dictating student investment behavior, followed by overconfidence and confirmation bias. This suggests that despite possessing adequate theoretical financial literacy through KSPM, social pressure and excessive self-belief remains the primary drivers in investment execution. The implications of this research suggest the necessity of integrating an investment psychology curriculum within Investment Galleries to mitigate the impact of cognitive biases and foster more rational and resilient young investors.